THE ROLE OF VILLAGE OWNED BUSINESS ENTITIES IN IMPROVING THE WELFARE OF VILLAGE COMMUNITIES - Syafii, Mochamad; Ulum, Bustanul; Rusdiyanto, Rusdiyanto; Pramitasari, Dini Ayu; Hasanah, Anisaul (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2023)
Devotion this analyze and evaluate mission development body effort owned by the village whose goal for move wheel village economy by optimizing village potential. If the village is able to optimize all its potential resources to drive the economy, then the development and strengthening management body effort owned by village expected able to develop business units and innovations that become new potentials in the village so that their mission body effort owned by village materialized , as driver of village life. Village owned body work put to use approach specifically intends to enhance the villagers' economic well-being through the growth of their business ventures. Village-owned formation body endeavor meant To use project programs run by the government and local governments mentioned in the previous sentence to push or accommodate economic activities that are submitted to be managed by the community as well as those that develop in accordance with local customs and culture in order to increase community income (1). The village-owned, on-budget base effort